Managing intellectual capital beneficial to firm performance - Noordin, Muhammad Arafat; Mohtar, Shahimi (2012)
Rapid changes are taking place at present, be it in social, technological, economic and political contexts.To meet these changes, firms need to be equipped with high quality knowledge and skills in order to be able to create opportunities, as well as innovate and sustain their businesses.On top of that, firms also have to constantly improve and manage their knowledge and skills, which are directly related to managing intellectual capital. This is because firms that obviously emphasized on intellectual capital development tend to be a step ahead and almost always possess state-of-the-art technology, which lead to greater innovation.Moreover, scholars also agreed that a firm's competitive advantage largely depends on its intellectual capital, or on its known ability to manage and utilize knowledge.Therefore, the recognition of intellectual capital has laid the groundwork to explore new practices of management.This paper will discuss on managing intellectual capital and its relationship with firm performance.